Pulmonary arterial hemodynamic in patients with or without pulmonary disease admitted after cardiac arrest - a sub study of the BOX trial. (3rd May 2023) - Arentz Taraldsen, I; Grand, J; Moeller, J E; Schmidt, H; Kjaergaard, J; Hassager, C
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Novo Nordisk Foundation Background: Patients with pulmonary disease may have altered pulmonary hemodynamic compared to patients without pulmonary disease. We hypothesize that these patients with pre-existing pulmonary disease have significantly elevated pulmonary arterial pressure during the first 48 hours of ICU-stay. Methods: The BOX-trial was an investigator-initiated, randomized, controlled study of targeted MAP (63 vs 77 mmHg) and PaO2 (9-10 vs 13-14 kPa) interventions in 789 comatose OHCA (of presumed cardiac origin) patients. Pre-existing, significant pulmonary disease was recorded at baseline. Patients underwent serial hemodynamic assessments with pulmonary artery catheter at time of insertion (0 h), 6 h, 12 h, 24 h, 36 h and 48 h. Among parameters recorded was cardiac output (CO). Pulmonary arterial pressures and central venous pressure were measured continuously. Patient characteristics included age, time to return of spontaneous circulation (ROSC) and initial rhythm. Results: Hemodynamic parameters from 730 patients were analysed, of which 89 (12%) had pulmonary disease. Of these, 57 (8%) had COPD, 26 (4%) had asthma and 6 (1%) had non-obstructive pulmonary disease. Patients with pulmonary disease were older (66±12 vs 62±14 years) and had similar time to ROSC (20±14 vs 23±16 minutes). Initial shockable rhythm was present in 73/89 (82%) with pulmonary disease and in 580/641 (90%) without, p=0.015. At 12 hours, mean pulmonary artery pressure (27±5 vs 24±6 p<0.0001, see Figure 1), systolic pulmonary pressure (36±7 vs 33±8 p=0.0004), and diastolic pulmonary pressure (21±5 vs 18±5 p<0.0001) were all significantly higher for patients with pulmonary disease than patients without. This association remain statistically significant, when adjusting for primary rhythm, time to ROSC and age. Also, heart rate (72±21 vs 66±17 bpm, p<0.0056) was significantly higher in patients with pulmonary disease. Cardiac index (cardiac output adjusted for body surface), central mixed venous saturation and CVP was similar between groups. Conclusions: Pre-existing pulmonary disease in resuscitated OHCA-patients is associated with significantly elevated pulmonary pressures. Figure 1